Relacje komunikacyjne typu "instant" w przestrzeni dydaktycznej = Instant relationship in the educational communication - Amborska-Głowacka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The concept discussed in the article is based on the assumption that polish pupil`s identity is built by autoreflection. The subject creates attributing meaning to his life and the style of interpretation different texts of culture. The school communication of all cultural texts must be a goal in itself.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie